An Evaluation about Physical Structure of Turcoman City Mosul in the Late Middle Age - Bakir, Abdulhalik (Ege Univ, 2010)
As known, cities are civilization cradle of history of mankind. Mosul was in a close geographic that there were mountainous regions and even Toros mountains. So it made easier a lot of things firstly construction works in Mosul. Mosul became focus point because it was an older city. In this paper, period that we examined was a period that Turkish states ruled. There was a successful and brilliant period in every field and especially about physical structure. But, in spite of these facilities, none of our geographers spoke about bridges, roads, councils except from government office, sport and amusements places, cereals stores, factories, churches and monasteries, tanneries and libraries. So deficiencies appeared. And also Mosul was a lively city for buildings and a trade city. We understand this from cities that built in the period of Seljuk and Atabegs. So we haven't got a chance to do an evaluation about these buildings. In spite of everything, we tried to draw a picture about the physical structure in the period of Turks in the late middle ages. In our paper, we transferred the information that geographers in the late middle ages presented and then studied to evaluate the information with other historical sources and researches.
Keywords: Mosul; Late Middle Age; City; Physical Structure; Mosul Atabegs